Estrategia psicopedagógica didáctica innovadora para el fortalecimiento de la lectoescritura en un estudiante de quinto año de educación general básica de la institución educativa Vicente Ramón Roca. - Mayorga Rizzo, Maria Fernanda (2025)
The purpose of this research was to design an innovative didactic psychopedagogical strategy to strengthen literacy in a fifth-year student of Basic General Education at the Vicente Ramón Roca educational institution, in the Quevedo canton. The student was identified as having difficulties in phonological awareness, auditory discrimination, reading comprehension, written production, and psycholinguistic skills, which affected her self-esteem and classroom participation. The design was based on theoretical approaches such as constructivism, meaningful learning, sociocultural theory, and psychopedagogical intervention models, with contributions from authors such as Piaget, Vygotsky, Ausubel, and Ferreiro. A qualitative, case study-type methodology was applied, utilizing interviews with the teacher and the administration of a diagnostic test to the student, allowing the characterization of her specific difficulties. Based on the findings, the "Lectoaventuras: Descubrir mi poder lectura" strategy was designed. It is based on multidimensional and progressive recreational activities aimed at developing language skills from an inclusive, motivating, and participatory approach. This proposal was validated by expert judgment, who confirmed its relevance and applicability in similar contexts. It was concluded that the strategy represents a viable alternative for addressing literacy, contributing to strengthening students' self-esteem, autonomy, and overall development, and is adaptable to other educational contexts with similar challenges. This work provides an innovative proposal within the field of psychopedagogy, promoting more personalized, equitable, and meaningful practices in the teaching-learning process.